Linked Nickel Oxide/Perovskite Interface Passivation for High‐Performance Textured Monolithic Tandem Solar Cells. Issue 40 (5th September 2021) - Zhumagali, Shynggys; Isikgor, Furkan H.; Maity, Partha; Yin, Jun; Ugur, Esma; De Bastiani, Michele; Subbiah, Anand S.; Mirabelli, Alessandro James; Azmi, Randi; Harrison, George T.; Troughton, Joel; Aydin, Erkan; et al.
Abstract: Sputtered nickel oxide (NiO x ) is an attractive hole‐transport layer for efficient, stable, and large‐area p‐i‐n metal‐halide perovskite solar cells (PSCs). However, surface traps and undesirable chemical reactions at the NiO x /perovskite interface are limiting the performance of NiO x ‐based PSCs. To address these issues simultaneously, an efficient NiO x /perovskite interface passivation strategy by using an organometallic dye molecule (N719) is reported. This molecule concurrently passivates NiO x and perovskite surface traps, and facilitates charge transport. Consequently, the power conversion efficiency (PCE) of single‐junction p‐i‐n PSCs increases from 17.3% to 20.4% (the highest reported value for sputtered‐NiO x based PSCs). Notably, the N719 molecule self‐anchors and conformally covers NiO x films deposited on complex surfaces. This enables highly efficient textured monolithic p‐i‐n perovskite/silicon tandem solar cells, reaching PCEs up to 26.2% (23.5% without dye passivation) with a high processing yield. The N719 layer also forms a barrier that prevents undesirable chemical reactions at the NiO x /perovskite interface, significantly improving device stability. These findings provide critical insights for improved passivation of the NiO x /perovskite interface, and the fabrication of highly efficient, robust, and large‐area perovskite‐based optoelectronic devices. Abstract : N719 dye molecules effectively link nickel oxide (NiO x )/perovskite interfaces by facilitating charge transport, concurrently passivating NiO x and perovskite surface traps, and forming a barrier that prevents undesirable chemical reactions occurring at the interface. The molecule also self‐anchors and conformally covers NiO x films deposited on complex surfaces, enabling fabrication of highly efficient textured monolithic p‐i‐n perovskite/silicon tandem solar cells.